The Influence of Promotions and Prices on The Purchase Decision of Mie Setan Noodle and Dimsum Gresik Products In The Future Covid-19 Pandemic - Arka Atyanto (International Journal of Review Management Business and Entrepreneurship (RMBE), 2023)
Mie Setan Gresik is one of the businesses affected by the COVID-19 pandemic. Mie Setan Gresik is engaged in food and baverage which sells various food and drinks, especially noodle dishes. The purpose of this study is to determine whether promotion and prices can influence consumer purchasing decisions during the Covid-19 pandemic. This study used quantitative with a sampling formula using purposive sampling. The results of this study are that prices and promotions can influence consumer purchasing decisions during the Covid-19 pandemic. This is indicated by the T-Test on the prices and promotions variables with values of 0.00 < 0.05.